Using active learning methodologies to teach sequenceanalysis and molecular phylogeny - Ortiz-Martín, Inmaculada; Del Espino Pérez, Ángel; García Luque, Estefanía; Viguera-Mínguez, Enrique (Wiley, 2024)
The great development of high-throughput molecular biology techniques and the consequent generation of massive data have made Bioinformatics essential for undergraduate Bioscience students. The importance of this scientific discipline is evidenced by the huge number of specialized publications, tools, and databases available. Training in Bioinformatics equips undergraduates with transferable skills that can be applied in all fields of Biology, such as programming abilities, data analysis, database management, biological knowledge, statistics, problem solving, and interdisciplinary collaboration. Over the past decade, there has been a notable increase in the number of higher education institutions worldwide that have adopted a competency-based curricula. This approach places a significant emphasis on the actions and skills that students are expected to develop, rather than merely focusing on the information, they are required to memorize. In this educational context, the use of active learning strategies has been demonstrated to enhance student comprehension and competency development. This paper describes the implementation of an active learning approach in a hands-on lesson performed by undergraduate students of Biology at the University of Malaga (Spain). Its main objective is to introduce students to molecular databases and information search systems on genes, proteins, and phylogeny. This is achieved within the framework of a smart campus, which integrates technological and sustainable resources to promote a positive and productive learning environment for the university community. This work presents the content and procedure of this practical activity, as well as the evaluation method and the results of a student survey to assess their opinions.
Keywords: Bioinformática; Active learning methods; Bioinformatics; Molecular databases; Molecular phylogeny